Effects of ephedrine, caffeine, and their combination on muscular endurance - Jacobs, I.; Pasternak, H.; Bell, D. G. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The purpose of this study was to investigate the effects of ingesting caffeine (C), ephedrine (E), and their combination on muscular endurance, using a double-blind, repeated measures design. METHODS: Ninety minutes after ingesting either C (4 mg x kg-1), E (0.8 mg x kg-1), a combination of C+E, or a placebo (P), 13 male subjects performed a weight-training circuit consisting of three supersets (SS), each SS consisting of leg press (at 80% of 1 RM to exhaustion) followed by bench press (at 70% 1-RM to exhaustion); 2 min of rest intervened between SS. RESULTS: The trials involving ephedrine ingestion (C+E and E), when compared with the nonephedrine trials (C and P), caused significant increases (P < 0.05) in the mean number of repetitions completed for both the leg-press and bench-press exercises but only during the first SS. During that first set, the mean number (+/-SD) of repetitions for leg press was 19 +/- 8, 16 +/- 7, 14 +/- 6, and 13 +/- 5 for the C+E, E, C, and P trials, respectively. The mean numbers of repetitions for the first set of bench-press exercise were 14 +/- 3, 13 +/- 3, 12 +/- 3, and 12 +/- 3 for the C+E, E, C, and P trials, respectively. As a result, the total weight lifted during all three sets was greater for the trials involving ephedrine ingestion. Systolic blood pressure before exercise was significantly increased with both ephedrine treatment trials when compared with the other trials (C+E = 156 +/- 29 mm Hg; E = 150 +/- 14; C = 141 +/- 16; P = 138 +/- 14). CONCLUSION: It was concluded that acute ingestion of C+E and E increases muscular endurance during the first set of traditional resistance-training exercise. The performance enhancement was attributed primarily to the effects of E; there was no additive effect of C.